Implementation of a Hepatitis B Screening Program in Patients Receiving Systemic Anti-Cancer Therapy - Jennifer Leigh; Ranjeeta Mallick; Stephanie Brule; Lisa Rambout; Jennifer Newton; Dominick Bossé; Curtis Cooper; Joanna Gotfrit (Current Oncology)
Cancer patients receiving non-endocrine therapies are at risk of hepatitis B virus (HBV) reactivation (HBVr). Guidelines recommend HBV screening prior to treatment. The Ottawa Hospital Cancer Center implemented a screening pilot for all patients receiving FOLFOX-based regimens between January and April 2023. We assessed the pilot from a quality improvement perspective. Charts were retrospectively reviewed, and patient and disease characteristics were collected. The primary endpoint was to identify the proportion of patients who underwent HBV screening prior to treatment start. Univariate analyses assessed the association between baseline characteristics and failure to screen. Quality metrics were also reviewed. There were 32/42 patients (76.2%) who completed screening, and 5 (11.9%) had a positive screen. The majority of eligible patients (59.5%) completed screening prior to the first treatment as intended. Four of five patients who tested positive were referred to Infectious Diseases. Of those, one received antivirals for chronic HBV. There were no treatment delays due to pending screening and no HBV reactivation. Receipt of prior systemic therapy was significantly associated with failure to screen (55 vs. 95%, OR 17.1 (95% CI 1.92–153), p = 0.011). The results of this pilot highlight the importance of building HBV screening into standardized treatment plans and engaging all team members to ensure high levels of screening. Prior systemic therapy receipt was associated with failure to screen, and thus, programs should include education on the necessity of screening as recommended by medical guidelines.